AI-DRIVEN FASHION DESIGN: HOW MACHINE LEARNING IS TRANSFORMING THE CREATIVE PROCESS - P., Selvi; M., Madhumitha; V.A., Shrimathi; R., Suresh (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The fashion industry is undergoing a transformative paradigm shift with the integration of Artificial Intelligence (AI) and Machine Learning (ML). These technologies are revolutionizing the creative process, enabling designers to innovate, streamline production, and meet evolving consumer demands. This paper explores how AI-driven tools are reshaping fashion design, focusing on three key areas: trend forecasting, design generation, and personalized styling, while also addressing sustainability and ethical considerations. AI-powered trend forecasting leverages vast datasets from social media, runway shows, and sales history to predict emerging styles with unprecedented accuracy. Machine learning algorithms, such as Convolutional Neural Networks (CNNs), analyse visual data to identify patterns and trends, while Natural Language Processing (NLP) extracts insights from customer reviews and fashion blogs. This data-driven approach reduces guesswork and enables brands to align their collections with consumer preferences. In design generation, Generative Adversarial Networks (GANs) are at the forefront of innovation. GANs enable the creation of unique patterns, textures, and garments by learning from existing designs. This not only accelerates the creative process but also opens new possibilities for experimentation. Reinforcement learning further optimizes production processes, minimizing waste and improving efficiency. Personalized styling is another area where AI excels. By analysing user data such as body measurements, style preferences, and purchase history, AI systems can recommend outfits tailored to individual tastes. This enhances the customer experience and fosters brand loyalty. However, the integration of AI in fashion is not without challenges. Ethical concerns, such as data privacy, algorithmic bias, and intellectual property rights, must be addressed. Additionally, the industry must ensure that AI-driven production aligns with sustainability goals. In conclusion, AI and ML are transforming fashion design by enhancing creativity, improving efficiency, and promoting sustainability. As these technologies evolve, they will continue to shape the future of fashion, offering exciting opportunities for innovation while necessitating careful consideration of ethical implications.